Innate immunity of the lung and adaptation to air breathing at birth - Whitsett, Jeffrey (Henry Stewart Talks, 2009)
Innate host defense of the lung, Stages of the developing lung, Diversity of airway epithelial cell types, Alveolar host defense, Surfactant composition, Respiratory distress syndrome, Genetic networks, Transcriptional networks and perinatal adaptation, Diseases of alveolar homeostasis, Histopathology of surfactant abnormalities, Pulmonary alveolar proteinosis, Alveolar macrophage cell lines, GM-CSF
Archived at 2021/02/25